Mechanization of tillage and harvesting operations for paddy production in Malaysia: challenges and potentials - Mat Nawi, Nazmi (Southeast Asian Regional Center for Graduate Study and Research in Agriculture, 2024)
Rice is a crucial food crop in Malaysia, being the staple food of the 31 million residents. However, the country’s annual rice production of 1.8 million MT can fulfill only about 70 percent of the national self-sufficiency level, while the remaining 30 percent is still being imported from other countries. Over the years, the Malaysian government has introduced several strategies to enhance the efficiency, productivity, and cropping intensity of the rice industry in the country. Such initiatives include promoting the full utilization of modern mechanization and automation technologies. Many studies have shown that adopting appropriate mechanization could minimize production costs, increase the yield, and improve product quality. Soil tillage and grain harvesting are the most energy-demanding and time-consuming operations in paddy production. As such, these two field operations have been fully mechanized in Malaysia. However, although mechanization can increase the productivity of paddy production, using heavy machines such as tractors and combine harvesters also poses challenges. For one, using such heavy machinery can cause soft soil condition and soil compaction and can damage the soil of the paddy field due to the high ground contact pressure pneumatic rubber tires of the machinery. Furthermore, using rubber tires on field machines leads to poor tractive performance and trafficability due to high slippage, thus increasing operating costs. Using a large combine harvester during the harvesting period can also cause several problems such as soil compaction, hardpan breakage, higher operational costs, higher grain losses, and limited access to a small paddy field. Moreover, a large combine harvester is difficult to transport from one place to another. The continuing revolution in mechanization technology has led to the introduction of new machinery for soil tillage and paddy harvesting, which can potentially overcome the existing challenges in mechanized paddy production. A new crawler-type tractor, which is relatively lighter and smaller than the conventional tractor, has been introduced for tillage. This type of tractor has higher tractive performance and lower operating cost than the traditional tractor. Likewise, a new medium-sized combine harvester equipped with rubber tracks has been recently made available in the market. This machine causes minimum soil damage and has been hinted to have better field performance and lower operating cost. However, before these newly introduced machineries can be fully adopted by the industry, their field performances should be evaluated by comparing them with those of the conventional equipment. Their impacts on the soil condition of the paddy field should also be investigated. These field measurements are important because the proper selection and management of machines are the key strategies to maximize field performance and to minimize machine operating costs. Alternatively, farmers could also adopt conservation agriculture methods. In conclusion, this paper provides an overview of the paddy production in Malaysia and reviews the current mechanization status in paddy production in the country, especially for tillage and harvesting operations. It also reviews the challenges in using the existing machinery and the potential solutions to those problems through the latest machinery technology.